A preliminary algorithm introducing immunogenicity assessment in the management of patients with RA receiving tumour necrosis factor inhibitor therapies - Garcês, Sandra; Antunes, Marília; Benito-Garcia, Elizabeth; da Silva, José Canas; Aarden, Lucien; Demengeot, Jocelyne (Annals of the rheumatic diseases, 2014)
Introduction Clinical remission is today the treatment goal for rheumatoid arthritis (RA), which requires fast and assertive therapeutic decisions for a tight control of disease activity. Few objective parameters are available to guide clinical decisions, particularly in switcher patients. We designed a preliminary algorithm introducing immunogenicity assessment in the current approach to patients with RA receiving tumour necrosis factor inhibitors (TNFi). Objective To evaluate the concordance between the new algorithm and current clinical practice, comparing the effectiveness of ‘immunogenicity-based’ versus ‘empirical-based’ switches in a cohort of patients with established RA receiving biologics. Methods EULAR therapeutic response was evaluated in 105 patients with RA (naive or switchers) over one year, through generalised estimation equation (GEE) analyses. Serum drug trough levels were assessed by ELISA and antidrug antibodies (ADAb) by Bridging ELISA. Results During follow-up, 48.6% of patients had therapeutic decisions concordant with the proposed algorithm (Group A), and 51.4% had discordant decisions (Group B). One year after the therapeutic decision, patients from Group A had a higher probability of achieving response (OR=7.91, p<0.001, 95% CI 3.27 to 19.13) and low disease activity (OR=9.77, p<0.001, 95% CI 4.69 to 20.37) than patients in Group B. Conclusions Immunogenicity assessment might help to optimise therapeutic decisions, leading to a better control of disease activity with significantly better clinical outcomes in patients with RA receiving TNFi.